Centrifuge Model Tests of the Effect of the Ground Motion Coherence Function on the Amplification of a Saturated Soil–Water Site. (15th May 2021) - Song, Xijun; Liu, Juan; Lan, Jingyan; Wang, Ting
Abstract : Two sets of dynamic centrifugal model tests were designed and implemented in this study: the overlying waterless surface and the water-covered surface. Based on the use of the El Centro waves with different intensities as the base input, the seismic time history at the surface of two sets of free site models was obtained. According to the results of the site response at two sets of the free site surface obtained with a traditional spectral ratio, the coherence functions at the surface and the base were used to modify the traditional spectral ratio for analysis and to evaluate the effect of the ground motion coherence function for site amplification. The modal characteristics and the amplification effect of a typical saturated soil water free site were summarized at the same time. The results showed that the ground response results of the two groups of typical free site centrifugal models were greatly influenced by the coherence function. In the low frequency phase, the coherence function of the amplification spectrum of the site response decreased significantly, while in the high frequency phase, the decrease trend decreased. The coherence function had a significant effect on the first-order mode of the free site. The first-order mode frequency and the amplification factor of a typical free site could be identified effectively. Compared with the saturated land free site model, the saturated soil water free site model had higher-order modes due to the overlying water. It was shown that the overlying water, as part of a complex medium system, could be ignored in the site response and basic cycle estimation.